Pengaruh Teknologi Digital, Religiusitas, Dan Sosial Media Terhadap Keputusan Generasi Z Berinvestasi Di Saham Syariah - Muhammad Rais; Himmatul Khairi; Faisal Hidayat (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2023)
This study was conducted to know the influence of technology, digital, religiosity, and social media on generation Z's decision to invest in Islamic stocks. All generation Z who invest in Islamic stocks are the population in the study while the research sample amounted to 100 people calculated by the Lemeshow formula with a confidence level of 95 percent. This research uses quantitative methods with multiple linear regression analysis models assisted by the SPSS 25 application. The results showed that partially digital technology, religiosity, and social media have a positive effect on the interest in investing in Islamic stocks in generation Z. While simultaneously showing that digital technology, religiosity, and social media have a positive effect on the interest in investing in Islamic stocks in generation Z. While simultaneously showing that digital technology, religiosity, and social media have a significant and positive effect on Islamic stock investment interest in generation Z with a significance contribution of 57.2 percent. The variable that has the greatest effect is social media. The development of digital technology, religiosity, and information from social media generates expectations from investors which can further increase the motivation to invest in Islamic stocks